Surgical Treatment of Acute Type A Aortic Dissection with 18-Litre Bleeding - Boldyrev, Sergey Y.; Barbukhatty, Kirill O.; Porhanov, Vladimir A. (AORTA, 2021)
Surgical treatment of Type-A acute aortic dissection is associated with high mortality and morbidity. One of the reasons is perioperative bleeding, which may lead to worse outcomes. We present a case of successful treatment of a patient with 18-litre perioperative blood loss in DeBakey Type-I acute aortic dissection with drug-induced hypocoagulation and malperfusion of a lower extremity.
Keywords: aorta; dissection; acute; bleeding